Effect of Roof Design Configurations On Natural Ventilation with an Obstacle Inside the Building Model - Moey, Lip Kean; Wan, Kian Shen; Tai, Vin Cent; Go, Tze Fong; Chong, Perk Lin (International Journal of Integrated Engineering, 2023)
Roof shape, roof angle, and internal obstacle are some of the factors that have a substantial impact on building’s ventilation performance. However, previous roof ventilation studies have not considered the influence of internal obstacle which can affect the overall building’s ventilation performance. For this study, CFD was used to study the effect of roof design configurations on natural ventilation with an obstacle inside the building model. The numerical simulation was carried out by using steady RANS equation specifically the Standard k-? with enhanced wall treatment. A total of 40 simulation cases were carried out. The study considered two roof shapes mainly the sawtooth roof and the saltbox roof with varying roof angle which were 10º, 20º, 30º, and 40º. Internal obstacles with various height were further added into the simulation cases. Next, grid sensitivity analysis was carried out using Grid Convergence Index (GCI) and Factor of two of observations (FAC2) analysis was carried out as model verification method to ensure a reliable simulation result. Based on the results, it is found that airflow characteristics such as wind speed, distribution of pressure coefficient, and flowrate of an isolated building are strongly dependent on the roof shape and roof angle. Next, the dimensionless flowrate (DFR) is measured to be highest with largest roof angle while lowest with smaller roof angle. Furthermore, the DFR of a building with internal obstacle is lower than that without an internal obstacle due to blockage of incoming air. Moreover, the results show that the sawtooth roof outperforms the saltbox roof in terms of measured parameter. Finally, the study concluded that an isolated building with higher roof angle and without an internal obstacle leads to the best dimensionless flowrate throughout the building.Roof shape, roof angle, and internal obstacle are some of the factors that have a substantial impact on building’s ventilation performance. However, previous roof ventilation studies have not considered the influence of internal obstacle which can affect the overall building’s ventilation performance. For this study, CFD was used to study the effect of roof design configurations on natural ventilation with an obstacle inside the building model. The numerical simulation was carried out by using steady RANS equation specifically the Standard k-? with enhanced wall treatment. A total of 40 simulation cases were carried out. The study considered two roof shapes mainly the sawtooth roof and the saltbox roof with varying roof angle which were 10º, 20º, 30º, and 40º. Internal obstacles with various height were further added into the simulation cases. Next, grid sensitivity analysis was carried out using Grid Convergence Index (GCI) and Factor of two of observations (FAC2) analysis was carried out as model verification method to ensure a reliable simulation result. Based on the results, it is found that airflow characteristics such as wind speed, distribution of pressure coefficient, and flowrate of an isolated building are strongly dependent on the roof shape and roof angle. Next, the dimensionless flowrate (DFR) is measured to be highest with largest roof angle while lowest with smaller roof angle. Furthermore, the DFR of a building with internal obstacle is lower than that without an internal obstacle due to blockage of incoming air. Moreover, the results show that the sawtooth roof outperforms the saltbox roof in terms of measured parameter. Finally, the study concluded that an isolated building with higher roof angle and without an internal obstacle leads to the best dimensionless flowrate throughout the building.